The influence of education in decision making concerning athlete's return to sport following a concussion injury: A systematic review. (July 2020) - Waterworth, Victoria; Procyk, Alexander; Canetti, Elisa; Hing, Wayne; Gough, Suzanne
Objectives: Concussions have emerged as one of the most prevalent and controversial injuries sustained within the sporting context. The objective of this review was to determine the influence that education has on decision making concerning athlete's return to sport following a concussion injury and if the risk is worth it in the eyes of the athletes. Study design: Systematic review. Methods: A rapid literature review was performed in PubMed, CINAHL, SPORTDiscus, Embase and Web of Science looking for articles that discussed concussions and any three of the four following search terms: (a) decision making, (b) education/knowledge, (c) sport/return to sport and (d) risk. Results: Sixteen of 1243 articles were included in this review based on eligibility criteria. Ten were cohort studies, four were cross-sectional studies and two were qualitative research. There was a good agreement between the authors for all studies when determining risk of bias, presenting a Cohen's κ of 0.901 (95% CI, 0.834, 0.968), p  <   0.001. Conclusion: Education can make a difference in athlete's decision making process to return to sport; however, their awareness of the health risks that they put themselves in by returning to sport too soon is clouded by other external and internal factors. What is not fully understood is why do they put themselves at this risk? Further studies should explore athletes' risk aversion behaviour and how it impacts their decision to return to sport following a concussion.